Ekstraterytorialne wykonywanie administracji publicznej - Kowalczyk, Barbara (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
Extraterritoriality constitutes an exception to the principle of territoriality of public administration and one of the manifestations of deterritorialism of national public administration. The development of performing tasks of public administration outside the territory of a given State is an inevitable consequence of internationalization (Europeanization) of administration and administrative law. Provisions of administrative law of the European Union as legal basis for exercise public administration modify fixed rules of extraterritoriality established by classical international law. These new forms of extraterritoriality can be regarded as further functional division of power (competence) and responsibility as well as new context of the concept of common (complex) administration of the European Union sensu largo.
Keywords: jurisdiction; deterritorialism; administrative cooperation; Frontex; extraterritoriality